(untitled) (Journal of Technology and Operations Management, 2017)
Mobile technology usage has changed way people work and becoming primary source of communication in the organization. There are few issues and challenges arise in the pursuit of work and personal life balance. Hence, it is important to highlight the antecedents and its effects on individual employee and organization in order to increase the organization efficacy and performance. The research aims to uncover the antecedents and effects of work connectivity after hours towards individual employee and organization as well as examining the underlying theory behind it. The method used by conducting Systematic Literature Review (SLR) in searching the keywords categorized under journals articles and magazines. The results shown in total of 120 related journal articles and magazines were mined based on the criteria that have been set. Only 16 articles were selected for the study after inclusion and exclusion decisions of the articles. Total numbers of five (5) databases were used in the searching process. In conclusion, work connectivity after hours issues have been intensively discussed based on previous existing literature. The highlighted issues can determine the organizational efficacy and effectiveness only if it is well managed and taken into consideration. Nevertheless, there are still rooms for improvement and opened for further discussion yet to obtain the utmost benefits out of it.